Pelaksanaan UKS di SD Muhammadiyah 1 Surakarta - Prasetyo, Ismail Jati, Drs. Muhroji, S.E, M.si (2017)
This study aims to describe: (1) planning of UKS in SD Muhammadiyah 1 Surakarta (2) implementation of UKS in SD Muhammadiyah 1 Surakarta (3) evaluation of UKS in SD Muhammadiyah 1 Surakarta. This research includes qualitative research with case study design. Techniques of collecting data using interviews, observation, and documentation. Test data validity by using source triangulation and method triangulation. Data analysis techniques with steps Data Collection (Data Collection), Data Reduction (Data Reduction), Data Display (Presentation Data), Conclusion Drawing / verification. The results of this study indicate that 1) the UKS program planning is implemented once a year ie the beginning of the semester by the UKS implementing team by adding / reducing the program in the last year which was then endorsed by the principal. 2) Program implementation activities cover 3 things: Health education is done by intrakurikuler carried out at school hours and extracurricular is done outside of lesson time. There are 3 activities of health services: "upgrading" activities covering small doctors and healthy canteen, "prevention" activities are immunization, routine child examination, "healing" ie P3K activities and light treatment. And Guidance of healthy school environment (PHBS) implemented 2 coaching namely mental and physical coaching. 3) Evaluation conducted at the end of the semester involves all the UKS implementing teams by conducting annual meetings.